Infection of bat and human intestinal organoids by SARS-CoV-2 - Zhou, Jie; Li, Cun; Liu, Xiaojuan; Chiu, Man Chun; Zhao, Xiaoyu; Wang, Dong; Wei, Yuxuan; Lee, Andrew; Zhang, Anna Jinxia; Chu, Hin; Cai, Jian-Piao; Yip, Cyril Chik-Yan; et al. (Nature medicine, 2020)
A novel coronavirus—severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)—emerged in humans in Wuhan, China, in December 2019 and has since disseminated globally 1 , 2 . As of April 16, 2020, the confirmed case count of coronavirus disease 2019 (COVID-19) had surpassed 2 million. Based on full-genome sequence analysis, SARS-CoV-2 shows high homology to SARS-related coronaviruses identified in horseshoe bats 1 , 2 . Here we show the establishment and characterization of expandable intestinal organoids derived from horseshoe bats of the Rhinolophus sinicus species that can recapitulate bat intestinal epithelium. These bat enteroids are fully susceptible to SARS-CoV-2 infection and sustain robust viral replication. Development of gastrointestinal symptoms in some patients with COVID-19 and detection of viral RNA in fecal specimens suggest that SARS-CoV-2 might cause enteric, in addition to respiratory, infection 3 , 4 . Here we demonstrate active replication of SARS-CoV-2 in human intestinal organoids and isolation of infectious virus from the stool specimen of a patient with diarrheal COVID-19. Collectively, we established the first expandable organoid culture system of bat intestinal epithelium and present evidence that SARS-CoV-2 can infect bat intestinal cells. The robust SARS-CoV-2 replication in human intestinal organoids suggests that the human intestinal tract might be a transmission route of SARS-CoV-2. Bat and human intestinal organoids can support replication of SARS-CoV-2, enabling further characterization of the virus lifecycle and investigation of potential mechanisms of enteric infection in COVID-19.